Coherent Pixel Design of Metasurfaces for Multidimensional Optical Control of Multiple Printing‐Image Switching and Encoding. (23rd October 2018) - Bao, Yanjun; Yu, Ying; Xu, Haofei; Lin, Qiaoling; Wang, Yin; Li, Juntao; Zhou, Zhang‐Kai; Wang, Xue‐Hua
Abstract: Printing image based on metasurface has attracted enormous research interests due to its subwavelength resolution, full‐color printing, and durable properties. Based on the spatially multiplexed pixels, the printing image using metasurface can be switched optically by altering the optical parameters, such as polarization and incident wavelength. However, such multiplexed pixel design has several problems, including the cross‐talk among different wavelengths, limitation to linear polarizations, and incapability for incident‐angle control. Here, a general method for pixel design, called the coherent pixel, which can overcome the problems and be used for multiple printing‐image switching controlled by arbitrary optical parameters (arbitrary incident angle, polarization, and wavelength) is proposed. Based on this coherent pixel, metasurface devices with novel functionalities can be realized, such as incident‐angle controlled and arbitrary polarization‐controlled printing images, which are not feasible with previous conventional pixel design method. The suitability and superiority of the coherent pixel for encryption application is also discussed. Such printing‐image switching controlled with arbitrary optical parameters should pave the way for various applications, including various functional switchable optical devices, image displays, and information encryption. Abstract : A coherent pixel design method is implemented for metasurface printing image switching under arbitrary optical conditions with different combinations of incident angle, polarization, and wavelength of light. Such a design not only stimulates metasurface devices with novel functionalities, such as incident‐angle controlled and helicity‐controlled printing images, but also enables encryption applications with improved security.